Facilitating In Vivo Articular Cartilage Repair by Tissue-Engineered Cartilage Grafts Produced From Auricular Chondrocytes. Issue 3 (March 2018) - Wong, Chin-Chean; Chen, Chih-Hwa; Chiu, Li-Hsuan; Tsuang, Yang-Hwei; Bai, Meng-Yi; Chung, Ren-Jei; Lin, Yun-Ho; Hsieh, Fon-Jou; Chen, You-Tzung; Yang, Tsung-Lin
Background: Insufficient cell numbers still present a challenge for articular cartilage repair. Converting heterotopic auricular chondrocytes by extracellular matrix may be the solution. Hypothesis: Specific extracellular matrix may convert the phenotype of auricular chondrocytes toward articular cartilage for repair. Study Design: Controlled laboratory study. Methods: For in vitro study, rabbit auricular chondrocytes were cultured in monolayer for several passages until reaching status of dedifferentiation. Later, they were transferred to chondrogenic type II collagen (Col II)–coated plates for further cell conversion. Articular chondrogenic profiles, such as glycosaminoglycan deposition, articular chondrogenic gene, and protein expression, were evaluated after 14-day cultivation. Furthermore, 3-dimensional constructs were fabricated using Col II hydrogel-associated auricular chondrocytes, and their histological and biomechanical properties were analyzed. For in vivo study, focal osteochondral defects were created in the rabbit knee joints, and auricular Col II constructs were implanted for repair. Results: The auricular chondrocytes converted by a 2-step protocol expressed specific profiles of chondrogenic molecules associated with articular chondrocytes. The histological and biomechanical features of converted auricular chondrocytes became similar to those of articular chondrocytes when cultivated with Col II 3-dimensional scaffolds. In an in vivo animal model of osteochondral defects, the treated group (auricular Col II) showed better cartilage repair than did the control groups (sham, auricular cells, and Col II). Histological analyses revealed that cartilage repair was achieved in the treated groups with abundant type II collagen and glycosaminoglycans syntheses rather than elastin expression. Conclusion: The study confirmed the feasibility of applying heterotopic chondrocytes for cartilage repair via extracellular matrix–induced cell conversion. Clinical Relevance: This study proposes a feasible methodology to convert heterotopic auricular chondrocytes for articular cartilage repair, which may serve as potential alternative sources for cartilage repair.